Shareholder Loans and Earnings Smoothing – Empirical Findings from German Private Firms. Issue 1 (1st January 2018) - Bigus, Jochen; Häfele, Stefanie
Abstract: This paper analyzes the interplay between shareholder loans and earnings smoothing in German private corporations. Shareholders who grant loans have a dual stakeholder role, being both equity holders and creditors. Those loans could be lost, because bankruptcy law requires their subordination in the event of bankruptcy. We therefore expect shareholder loans to mitigate agency problems of debt. This reduces the need for debt covenants and earnings smoothing. Moreover, the interest payments from shareholder loans tend to lower payout volatility which also reduces the need for dividend and earnings smoothing. We expect and find that private firms with shareholder loans exhibit significantly lower levels of earnings smoothing than other private firms. We find that with a 10 percentage-point increase in the shareholder loans to total assets ratio, earnings smoothing decreases by about 10% of the mean value. We also find that this substitution effect usually occurs in case of managerial ownership and tends to be slightly weaker in the event of dispersed ownership. The results are robust for different econometric specifications, including different measures of key variables and propensity score matching. The paper suggests that financial reporting by private firms responds to the dual stakeholder role of shareholder loans.